1983
DOI: 10.1051/agro:19830601
|View full text |Cite
|
Sign up to set email alerts
|

Piégeage sexuel de la processionnaire du pin, Thaumetopoea pityocampa Schiff. (Lep., Notodontidae) par des attractifs de synthèse. Premiers essais dans le Sud-Ouest de la France

Abstract: Pierroton, F 33610 Gazinet. RÉSUMÉ Une phéromone sexuelle attractive, l'acétoxy-1 hexadécen-13 (Z) yne-11, a été identifiée récemment chez la femelle vierge de Thaumetopoea pityocampa Schiff. Dans la présente étude, l'attractivité sur le terrain de ce composé est démontrée et comparée à celle de l'isomère E. Par ailleurs, des effets de dose, de hauteur et de bordure sont mis en évidence dans le but d'une optimisation du piégeage. Enfin, les premières comparaisons entre piégeage sexuel et piégeage lumineux sont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Zhang & Paiva (1998) noted that, in central and southern Portugal, the species has only one generation. Similarly, Einhorn et al. (1983) in southwestern France and Tiberi & Niccoli (1984) in Italy, reported the species to be univoltine.…”
Section: Discussionmentioning
confidence: 85%
“…Zhang & Paiva (1998) noted that, in central and southern Portugal, the species has only one generation. Similarly, Einhorn et al. (1983) in southwestern France and Tiberi & Niccoli (1984) in Italy, reported the species to be univoltine.…”
Section: Discussionmentioning
confidence: 85%
“…Einhorn et al . () found that pheromone traps positioned on the edges of pine stands captured significantly more male pine processionary moth than traps situated within the interior of the pine stand and Houri and Doughan () found that a trap located closer to the forest edge captured more eastern pine processionary Thaumetopoea wilkinsoni (Tams) moths than a trap located within the forest. Athanassiou et al .…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory analyses as well as wind tunnel and field experiments, Z13,11yne-16:OAc has been demonstrated to be a pheromone component of T. pityocampa (Guerrero et al 1981;Cuevas et al 1983;Einhorn et al 1983). Careful reinvestigation of the T. pityocampa pheromone (Quero et al 1997) seems to suggest that this unusual compound may indeed be the single-component sex pheromone of T. pitycampa.…”
Section: Resultsmentioning
confidence: 96%